Risk factors and management of biliary stones after living donor liver transplant and its effect on graft outcome - Dabbous, Hany; Elsayed, Ashraf; Salah, Manar; Montasser, Iman; Atef, Mohamed; Elmetenini, Mahmoud (Frontiers in Medicine, 2022)
Background: Bile stones are associated with numerous complications in liver transplant recipients. Endoscopic Retrograde Cholan¬gio Pancre¬atography (ERCP) has been proven to be safe and highly effective in dealing with most post-transplant biliary complications. Objective: To identify the possible risk factors for bile stone formation on top of biliary stricture, the effects of stones on graft outcomes, and their management. Methods: This case control study included 83 patients who underwent living donor liver transplant and suffered from postoperative biliary stricture with or without stones. Patients were divided into two groups. Group 1 (n=55) included patients with biliary strictures with no stones and group 2 (n=28) included patients who developed stones on top of biliary strictures. Data about the recipient and donor characteristics, surgical technique, blood lipid profile, immunosuppressive drugs, post-transplant complications, and the interventions were collected from the medical records. Results: The frequency of hepatitis C virus was significantly higher in group 2 compared to group 1 (71.4% versus 47.3%, p=0.036). The body mass index (BMI) of the donors was significantly higher in group 2 than in group 1 (25.17±2.53 versus 23.68±2.63, p=0.015). Episodes of acute rejection were significantly higher in group 2 than in group 1 (21.4% versus 5.5%, p=0.027). The ERCP was sufficient in most of the cases (89.2%) to ensure biliary drainage. Conclusion: Hepatitis C virus infection and the high BMI of the donors were the significant risk factors for developing bile stones on top of biliary strictures. Biliary stones were associated with high episodes of acute graft rejection, and they could be successfully managed by ERCP modality.